Explaining business failure through determinist and voluntarist perspectives - Çera, Gentjan; Belas, Jaroslav; Zapletalikova, Eliska (Serbian Journal of Management, 2019)
The aim of this study is to investigate factors that can prevent business failure by using determinist and voluntarist perspectives collectively. Both views implicate numerous theories such as institutional theory, industry life cycle theory, resource-based view, emotive approach etc. This research is conducted on a firm-level data collection through a survey. The current study uses principal component analysis and hierarchical logistic regression to test the proposed hypotheses in an original dataset of small and medium-sized enterprises (SMEs) operating in Central Europe. The results demonstrated that facing institutional constraints and internal difficulties can lead to business failure. Firms in growth phase of business cycle are less likely to fail as compared to their counterparts in establishment phase. At the individual level, having entrepreneurial experience diminish the fail chances for a firm. Moreover, failure is less prone to occur for bigger firms and those that operate as business-to-business (B2B). The current research contributes to enriching the literature of the field by offering evidence on how to avoid failure. This paper provides useful insights for both managers and policymakers who are responsible for designing policies and strategies to boost entrepreneurship.